2022
DOI: 10.1002/inf2.12296
|View full text |Cite
|
Sign up to set email alerts
|

Single‐atom catalysts supported on ordered porous materials: Synthetic strategies and applications

Abstract: Single-atom catalysts (SACs) are attracting extensive attention due to their incredibly catalytic activity and selectivity, high utilization of metal atoms, and obvious cost reduction. The unique ordered porous materials (OPMs) are promising carriers for stabilizing single atoms due to their large surface areas and uniformly tunable pore sizes. Meantime, the geometric and electronic structures of single-atom metals can be tuned by the interaction between the single-atoms (SAs) and OPMs to enhance the catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 136 publications
0
29
0
Order By: Relevance
“…Moreover, 5-sulfosalicylic acid worked as the stabilizing agent, leading to the generation of very fine zirconia particles with the diameter of <2 nm in meso-Zr-SA15 ( Figure 2 f). Generally, heterogeneous catalysis occurred on the surface of metal particles, and the decrease in the size of metal particles resulted in a higher fraction of surficial atoms available, thus bringing about improvement on the catalytic performance [ 45 ]. The blank control experiment showed that 20.1% of furfural was converted with no furfuryl alcohol yield ( Table 2 , entry 6).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, 5-sulfosalicylic acid worked as the stabilizing agent, leading to the generation of very fine zirconia particles with the diameter of <2 nm in meso-Zr-SA15 ( Figure 2 f). Generally, heterogeneous catalysis occurred on the surface of metal particles, and the decrease in the size of metal particles resulted in a higher fraction of surficial atoms available, thus bringing about improvement on the catalytic performance [ 45 ]. The blank control experiment showed that 20.1% of furfural was converted with no furfuryl alcohol yield ( Table 2 , entry 6).…”
Section: Resultsmentioning
confidence: 99%
“…Advanced atomic-level characterization techniques and theoretical methods, such as high-resolution high-angle annular darkfield scanning transmission electron microscopy (HAADF-STEM) images, X-ray absorption spectroscopy (XAS), Raman spectroscopy and DFT calculations have been gradually applied to the characterization and study of SACs. 150,151 In this section, we focus on two techniques, HAADF-STEM and XAS.…”
Section: Experimental Characterizationsmentioning
confidence: 99%
“…5,6 Thus, many efforts have been devoted to developing highly performed water electrolysis and satisfying the demands for carbon-neutral initiatives. [7][8][9][10] Generally, excellent HER activity will occur on the dedicatedly designed electrocatalysts. Since the electrocatalysts go through extra voltage to overcome the energy barrier for HER, it is crucial to develop novel electrocatalysts with small overpotentials to reduce energy consumption and improve energy conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Integrating HER and the intermittent electricity generated from those renewable energy resources represents a promising future for energy storage of renewable energies in the form of chemical energy 5,6 . Thus, many efforts have been devoted to developing highly performed water electrolysis and satisfying the demands for carbon‐neutral initiatives 7–10 …”
Section: Introductionmentioning
confidence: 99%